An Applıcatıon For Treatment Of Ectopıc Eruptıon - Deniz Sağdıç; Yalçın Işımer; Ünsal Ünal (Galenos Yayinevi, 1989)
Sometimes a maxillary permanent first molar, eruptsmesially and causes both rezorption on primary second molar and uncompletetion its eruption. Consequently, this will end up early loss of primary second molar and loss of space in the arch length. It has been suggested several methods for ectopic eruption treatment. In this article, we would like to advocate an appliance which is simple, effective and easy to fabricate for early treatment of ectopic eruption.